Pengembangan Sistem Informasi Manajemen Alat Pada Laboratorium Instrumentasi dan Pengukuran Fakultas MIPA Universitas Brawijaya - Willy Aditya Nugraha; Ahmad Afif Supianto; Welly Purnomo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Laboratory of Instrumentation and Measurement is one of the laboratories in the Department of Physics, Faculty of Mathematics and Natural Sciences, Brawijaya University. This laboratory serves student practicum activities, lecture and student research, and research activities such as workshops and demos. To conduct data inventory of laboratory equipment, borrowing and returning equipment service, laboratory staff still using manual records in spreadsheet and forms. There are several problems such as manual records for the equipments, the synchronization of the data owned by the laboratory staff and the head of the laboratory, and also the laboratory staff must find the form from all loan forms when returning. Based on this, an inventory management information system is needed for laboratory equipment that can help solve the problem of inventory, adding information to equipment, and borrowing and returning equipment. The development of this information system uses the SDLC Evolutionary Prototyping model that allows improvement of functionality during continuous iterations. The results of the requirement analysis are described using use case diagrams and activity diagrams. The implementation of this information system uses the CodeIgniter PHP framework. System testing is done by using validation testing with the results of testing all functions that can be done properly and verified validly. The result of compatibility testing shows some problems, such as critical issue found because of the SSL or HTTPS feature that is not activated and major and minor problems exist because some browsers don't support some CSS properties. UAT testing resulted in an acceptance percentage of 91.8% for administrator actors and 83.6% for student actors.